When good vaccines go wild: Feral Orthopoxvirus in developing countries and beyond - Nissin Moussatché,1,2 Clarissa R. Damaso,2 and Grant McFadden1 (The Journal of Infection in Developing Countries, 2008)
The presence of zoonotic poxviruses in nature represents a potential human health risk that has to be re-evaluated by health authorities not only in developing countries, but also in many developed countries. For example, buffalopox virus infection remains to be a threat to humans and cattle in India, and monkeypox virus infection persists in several inhabited places in Africa and, more recently, in the USA. There are also a great number of zoonotic transmissions of cowpox virus from cats to humans in Europe. For almost a decade in Brazil, vaccinia-like viruses have been isolated from human and cattle infections. This review examines the ability of potentially pathogenic orthopoxviruses, including feral versions of vaccinia virus vaccine, to persist in nature and re-emerge for reasons we do not yet understand.